2020
DOI: 10.1186/s12958-020-00646-4
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of predictors of fertility outcomes in men with non-obstructive azoospermia undergoing microdissection testicular sperm extraction

Abstract: Background: Microdissection testicular sperm extraction (microTESE) in men with non-obstructive azoospermia (NOA) is the procedure that results in the highest number of sperm cells retrieved for in vitro fertilization (IVF). This study presents a novel assessment of predictors of sperm retrieval as well as downstream embryology and pregnancy outcomes in cases of men with NOA undergoing microTESE. Methods: A retrospective chart review of 72 men who underwent microTESE for predictors of fertility outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…The advent of microTESE significantly improved the odds for these couples to have an opportunity to conceive with autologous gametes. The odds of sperm retrieval with microTESE have been associated with severity of the testicular histopathological architectural pattern in the parenchyma of the testis [8][9][10][11][12][13]. The outcomes of the men in this study were consistent with a significantly higher sperm retrieval rate of 91.7% in men with favorable histopathological patterns as opposed to 56% sperm retrieval rates in the men with unfavorable histopathological patterns.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The advent of microTESE significantly improved the odds for these couples to have an opportunity to conceive with autologous gametes. The odds of sperm retrieval with microTESE have been associated with severity of the testicular histopathological architectural pattern in the parenchyma of the testis [8][9][10][11][12][13]. The outcomes of the men in this study were consistent with a significantly higher sperm retrieval rate of 91.7% in men with favorable histopathological patterns as opposed to 56% sperm retrieval rates in the men with unfavorable histopathological patterns.…”
Section: Discussionsupporting
confidence: 55%
“…The most severe histopathology is Sertoli cell only pattern, characterized by entirely absent germ cells with only Sertoli cells visible in the germinal epithelium by low-power light microscopy. It has been demonstrated that men with more severe histopathological architecture have lower sperm retrieval rates [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, what these previous studies had in common was a prediction of sperm retrieval rate [ 12 ]. The clinical efficiency of different testicular sperm extractions on the embryo development and clinical pregnancy rates of azoospermic men have been rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…For predictors of SRR, patient age, serum hormone levels, and testicle size have been evaluated, however, conclusive evidence is lacking that any of these factors is predictive of successful sperm retrieval [ 67 , 68 , 69 ]. Testicular histopathology does provide some prognostic information for SRR, but it is not routinely recommended for diagnosis of NOA, as the diagnosis can be made clinically based on FSH > 7.6 and testis length < 4.5 cm in about 90% of men with this condition [ 22 , 68 , 70 , 71 ]. Similarly, no clinical or biochemical factors have been found to be predictive of ICSI outcomes [ 3 ].…”
Section: Intracytoplasmic Sperm Injection For Noamentioning
confidence: 99%